Implementasi Model PBL berbasis Culturally Responsive Teaching dalam Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar - Hidayah, Nurul; Putri, Kharisma Eka; Rohmawati, Novi (Jurnal Simki Postgraduate, 2025)
This study aims to improve student learning outcomes on the material "My Pride, My Region" through the application of the Problem Based Learning (PBL) model based on Culturally Responsive Teaching (CRT) in class V SDN Gayam 1. The study used the Classroom Action Research (CAR) method which was implemented in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The subjects of the study were 27 students of class V, consisting of 12 males and 15 females. Cycle I used the PBL model with large group discussions, while in cycle II more effective small group discussions were applied, accompanied by learning media in the form of cultural videos, LKPD, and mini projects. The instruments used were observation sheets to measure student involvement and focus and written tests to measure cognitive learning outcomes. The results showed that student learning completeness in cycle I only reached 59.3% or 16 out of 27 students met the Minimum Completion Criteria (KKM). After improvements were made in cycle II, learning completeness increased significantly to 85% or 23 students achieved KKM. In addition to improving learning outcomes, students' active involvement and self-confidence also increased significantly.